Kajian perbandingan ram lengkung dan ram rata bagi pemusar udara aliran jejarian dalam mengurangkan emisi - Mohd. Jaafar, Mohammad Nazri; Samat, Ismail; Abdul Mookmin, Muhamed Shukri (The Institution of Engineers, Malaysia, 2005)
Gas turbine engines are widely used either in the industrial or the aviation sector. The engine efficiency is one of the maincriteria in selecting the suitable engine. The combustor or the combustion chamber is one of the key components in gas turbineengines and is given special attention by many researchers in engine development. A good combustor is able to providecomplete combustion with very minimal emissions production. This can be achieved by using air swirler. Through this study,an experiment was conducted to investigate the effectiveness of applying curved blade radial air swirler with different bladeangles over straight blade. The level of emissions produced were measured and compared for the two types of blade, curvedand straight. Experimental results obtained showed that the curved blade design produces lower level of emissions comparedto that of straight blade. Emission reduction of 36%, 67%, and 67% for NO , CO and SO emissions, respectively were achievedwhen using curved blades air swirler compared to that of straight blades. These were all achieved at blade angle of 60o